Changes in Live Weight Across Age Dynamics of Offspring Obtained from Mating Camelus Dromedarius And Camelus Bactrianus Camels - Turganbaev. R.U.; Ko'charov. S.Y (American Journal Of Agriculture And Horticulture Innovations, 2025)
This article determines and draws conclusions on the changes in live weight across age dynamics of offspring obtained from mating Camelus dromedarius and Camelus bactrianus camels in various pasture conditions of the Ustyurt Plateau in the Republic of Karakalpakstan.